An inverse problem for a nonlinear Schrödinger equation. (21st August 2002) - Ton, Bui An
Abstract : We study the dependence on the controlq of the interval of definition of the solutionu of the Cauchy problemι u ′ + Δ   u = − λ | u |   2 u − ι q u inℝ   2 × ( 0, T ), u ( x, 0 ) = ω inℝ   2, and we prove a version of Fibich's conjecture. Feedback laws for an inverse problem of the above equation with experimental data, measured on a portion of the boundary of an open, bounded subset ofℝ   2 are established.